Analisis Usability Pada Website Aplikasi Viu menggunakan Performance Measurement, Retrospective Think Aloud dan User Experience Questionnaire - I Gede Putu Krisna Adi Sastrawan; Desak Ayu Sista Dewi (PT. Hasba Edukasi Mandiri, 2025)
Viu is a video service that provides Asian drama series. However, in its operation, there are several complaints submitted by users through feedback provided on the Google Playstore page. Therefore, a comprehensive usability analysis is needed on the Viu application website to identify problems by measuring the effectiveness and efficiency of the system and user satisfaction. This study involved 6 participants obtained from the results of pilot testing using the Good Turing (GT) discounting procedure calculation. Data processing in this study was carried out using the Performance Measurement technique to measure the effectiveness and efficiency of the system, as well as Retrospective Think Aloud and User Experience Questionnaire to measure aspects of user satisfaction. The results of the Performance Measurement evaluation showed that the Viu application website was very effective because the total effectiveness of website use was 95.24%. In measuring the level of efficiency, a time-based efficiency value of 0.0099 goal/sec was obtained and in measuring overall relative efficiency, an average result of 92.07% was obtained. The six aspects of user experience obtained an average value of the clarity aspect (perspicuity) of 1.63. While the novelty aspect was 0.63. Furthermore, the attractiveness aspect is 0.50, the efficiency aspect is 0.17, the dependability aspect is 0.13 and the stimulation aspect is 0.04. The recommendations generated from Retrospective Think Aloud consist of 4 recommendations.